Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/bjs/znaa160
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of radioguided occult lesion localization using 125I seeds versus hookwire localization before breast-conserving surgery for non-palpable breast cancer

Abstract: Background The aim was to determine the cost-effectiveness of radioguided occult lesion localization using 125I-labelled seeds (125I seeds) versus hookwire localization in terms of incremental cost per reoperation avoided for women with non-palpable breast cancer undergoing breast-conserving surgery. Methods This study was based on a multicentre RCT with eight study sites comprising seven public hospitals and one private hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This is the first published study to date that assessed both surgical outcomes and costs between RL and WL in WLE for early-stage breast cancer. 25 The results support previous findings that there was no significant difference in surgical outcomes between RL and WL techniques. 2 , 3 , 8 11 It also demonstrated that WLE using RL was a cost-effective technique for reducing delays in surgery related to preoperative localisation with WL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is the first published study to date that assessed both surgical outcomes and costs between RL and WL in WLE for early-stage breast cancer. 25 The results support previous findings that there was no significant difference in surgical outcomes between RL and WL techniques. 2 , 3 , 8 11 It also demonstrated that WLE using RL was a cost-effective technique for reducing delays in surgery related to preoperative localisation with WL.…”
Section: Discussionsupporting
confidence: 90%
“…The costs involved with a new technology compared to current “gold standard” is a crucial consideration in its adoption. 25 Compared with most wireless techniques, WL is economical. 29 31 RL requires additional expenditure, including consideration of upfront costs of the console and guidance probe.…”
Section: Discussionmentioning
confidence: 99%
“…NWNI techniques need an early capital expenditure for the intraoperative detection equipment to be used and most of the cost savings are indirect: the most noticeable, if compared with RSL, is the unnecessary involvement of nuclear medicine personnel and resources. All the cited techniques have direct and indirect costs that shall be carefully evaluated for their cost assessment, as done in several papers [ [79] , [80] , [81] , [82] , [83] , [84] ]. It is noteworthy that all cost-savings (both direct and indirect) can vary from institution to institution depending on several logistic factors, such as the location of the theatre and admission wards, the radiologists’ workloads, the structure of the clinics, and the cancer workload.…”
Section: Discussionmentioning
confidence: 99%
“…ROLLIS has a number of advantages over HWL, including lack of movement after insertion, 21 improved patient satisfaction, 22 higher ease of use by radiologists and surgeons, 23 more efficient use of radiology and theatre booking 24 and higher cost effectiveness 25 . Although we have not been able to show a significant difference in overall cosmetic outcomes for women having BCS guided by ROLLIS compared with HWL, the lack of demonstrable detrimental effect adds further evidence to support increased uptake of ROLLIS for pre‐operative localization prior to BCS.…”
Section: Discussionmentioning
confidence: 99%